What is behind the quality assessment of university research? Towards another research culture - Pomares Cintas, Esther (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
The world of the university has been greatly affected by the leadership and the legacy of the new model of public management associated with the domination of technologies tied to the digitalization of society. The impact on the emancipation of university research in its quest for knowledge, and on the orientation of the public university toward the progress of knowledge and its transmission to students and to society, has challenged its foundations. Spaces of reflection do not officer this model the promise of high performance, nor do “slow science” or perennial great works find their way into the grammar of the public university. The public agencies of externalization of the evaluation of university research have intervened in the quality of scientific production, importing parameters (claves) that confine and reify research activity: indices of quality, such as the so-called “impact factor” as a seal of guarantee, are under the control of private enterprise, which conceives quality in the terms of a “product”, that is, research as just one more commodity on the university market. Through the tautological logic of the realm of numbers, in which the public university and researchers assume a role of customers (clients), the university appears as a “brand” corresponding to the parameters of competitiveness and profitability, with the ultimate objective of attracting investors, raising funds, and attracting students as clients.
Keywords: Agencies of externalization, impact factor, university research, customer’s market, source funding